Position Control of DC Motor by Self Tuned Fuzzy PID Controller - Singh, Barjinder (My University, 2012)
Both DC and AC motors have been extensively used in control systems but each has its own characteristics. The main advantages of DC motors are easy speed and position control. DC motors have become the preferred choice in many industrial applications such as robot control, welding, roll process, etc. There is a strong interest to develop new control tools to enhance their performance and their intelligence. The aim of this thesis is to design a robust method of position control of DC motor. There are three kinds of DC motor position control: Classic method such as PID controllers in which the big limitation can be seen if the parameter of the system is changed, modern style such as adaptive controller which is time consuming as identification process is added to the process and intelligent method as fuzzy controller and neural networks show better performance. As new researches show, the fuzzy controllers give a good performance in the presence of noise. In this thesis we take three controller PID controller, Self tuned Fuzzy PID controller and Two self tune Fuzzy PID controller. Comparison of the different kinds of controllers are analyzed in the thesis. It was found that the proposed controller overcome uncertainly and reduces the error.
Keywords: Fuzzy PID Controller